SOCIAL ETHIC OF MAHATMA GANDHI AND MARTIN BUBER: . - Henry, Sarojini (Journal of Dharma, 1991)
In the first week of March 1939, Martin Buber wrote a letter to Mahatma Gandhi in reply to Gandhi's article, "The Jews," published in his prestigious weekly, Harijan, dated 26th November 1938. Gandhi had suggested that the Jews in Germany use Satyagraha or soul-force as the most effective weapon against Nazi persecution. Gandhi had further expressed his concern over the Jewish-Arab problem